2021
DOI: 10.1080/10717544.2021.1963351
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid-modified ROS-responsive nanoparticles encapsulating luteolin for targeted breast cancer treatment

Abstract: Luteolin (Lut) is a natural flavonoid polyphenolic compound with multiple pharmacological activities, such as anti-oxidant, anti-inflammatory, and anti-tumor effects. However, the poor aqueous solubility and low bioactivity of Lut restrict its clinical translation. Herein, we developed a reactive oxygen species (ROS)-responsive nanoplatforms to improve the bioactivity of Lut. Folic acid (FA) was employed to decorate the nanoparticles (NPs) to enhance its targeting ability. The size of Lut-loaded ROS-responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…The authors also evaluated the NPs’ efficacy in vivo and found that FA modification enhanced the anti-tumor activity of Luteolin-loaded NPs. These results were in accordance with the in vitro anti-tumor efficacy results [ 55 ]. In another study, Sriraman et al evaluated different liposomal formulations for their targeting ability and anti-tumor efficacy in vitro, spheroids, and in vivo.…”
Section: Resultssupporting
confidence: 92%
“…The authors also evaluated the NPs’ efficacy in vivo and found that FA modification enhanced the anti-tumor activity of Luteolin-loaded NPs. These results were in accordance with the in vitro anti-tumor efficacy results [ 55 ]. In another study, Sriraman et al evaluated different liposomal formulations for their targeting ability and anti-tumor efficacy in vitro, spheroids, and in vivo.…”
Section: Resultssupporting
confidence: 92%
“…It helps to reduce the epidermal growth factor-induced markers as well as restoration of cell-cell junctions [1,7]. LT-loaded nanoformulations such as folacin-modified nanoparticle [8], nanoparticles [9,10], NLCs [11], folic acid-modified ROS-responsive nanoparticles [12], and nanospheres [13] have been prepared and enhanced bioavailability and efficacy have been reported. However, the application of LT vesicles in the skin cancer has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work reported a self-assembly strategy to produce Oxi-αCD NPs (ROS-responsive drug carriers), which exhibited good biocompatibility and could be used as excellent drug delivery carriers ( Zhang et al, 2015 ; Wang et al, 2019 ; Ni et al, 2020 , Wang et al, 2021c .). Briefly, lecithin and DSPE-PEG 2000 were dispersed in anhydrous ethanol and ultrapure water.…”
Section: Methodsmentioning
confidence: 99%